Induced osteogenic differentiation of human smooth muscle cells as a model of vascular calcification - Pustlauk, Wera (Sci Rep, 2020)
Vascular calcification is a severe pathological event in the manifestation of atherosclerosis. Pathogenic triggers mediating osteogenic differentiation of arterial smooth muscle cells (SMC) in humans remain insufficiently understood and are to a large extent investigated in animal models or cells derived thereof. Here, we describe an in vitro model based on SMC derived from healthy and diseased humans that allows to comprehensively investigate vascular calcification mechanisms. Comparing the impact of the commonly used SMC culture media VascuLife, DMEM, and M199, cells were characterised by immunofluorescence, flow cytometry, qPCR, and regarding their contractility and proliferative capacity. Irrespective of the arterial origin, the clinical background and the expansion medium used, all cells expressed typical molecular SMC marker while contractility varied between donors. Interestingly, the ability to induce an osteogenic differentiation strongly depended on the culture medium, with only SMC cultured in DMEM depositing calcified matrix upon osteogenic stimulation, which correlated with increased alkaline phosphatase activity, increased inorganic phosphate level and upregulation of osteogenic gene markers. Our optimized model is suitable for donor-oriented as well as broader screening of potential pathogenic mediators triggering vascular calcification. Translational studies aiming to identify and to evaluate therapeutic targets in a personalized fashion would be feasible.